The early Enoch literature - Boccaccini, Gabriele, 1958-; Collins, John Joseph, 1946- (Supplements to the Journal for the study of Judaism ;, 2007)
In recent years there has been a lively debate about the early Enoch literature and its place in Judaism. This volume is intended to represent that debate, by juxtaposing pairs of articles on several key issues: the textual evidence, the relationship to the Torah, the calendar, the relation to wisdom, the relation to the temple, the sociological setting and the relation to the Dead Sea Scrolls. It is not the intention of the editors to impose a consensus, but rather to stimulate discussion by bringing together divergent viewpoints. The book should be a useful textbook not only on the Enoch literature and apocalypticism, but more generally on Second Temple Judaism.